2015
DOI: 10.1002/pat.3427
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol: a promising agent for nanodispersion and compatibility of EVA/organomodified montmorillonite nanocomposites

Abstract: *Ethylene-vinyl acetate (EVA) nanocomposites were extruded with two types of organomodified montmorillonite (OMMT) and 1 wt% glycerol. The characterization of the nanocomposites was performed by transmission electron microscopy, X-ray diffraction, differential scanning calorimetry, and dynamic mechanical analysis. The experimental results revealed that glycerol improved the Cloisite 30B clay exfoliation and promoted a rise in aspect ratio of the Cloisite 20A clay. In the rubbery region, the EVA/G showed a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
(37 reference statements)
0
4
0
1
Order By: Relevance
“…It is noteworthy that transitions around 44°C were exhibited for all the three foams and were due to the transition of EVA regardless of the types and contents of EVA. 18 21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that transitions around 44°C were exhibited for all the three foams and were due to the transition of EVA regardless of the types and contents of EVA. 18 21…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that transitions around 44 C were exhibited for all the three foams and were due to the transition of EVA regardless of the types and contents of EVA. [18][19][20][21] Damping properties were investigated by measuring DMA. The magnitude of damping can be determined from the dynamic mechanical behavior, in which tan d was used as a measure of damping.…”
Section: Effect Of Poe Contents On Resilience Dynamic Stiffness Andmentioning
confidence: 99%
“…This would lead to increased clay dispersion within the polymer matrix. As described in the literature, [21,26] EOs can act as plasticizers, increasing chain mobility by weakening the intermolecular interactions; thus, allowing the penetration of polymer chains into MMT interlamellar space.…”
Section: X-ray Diffraction Of the Bionanocompositesmentioning
confidence: 98%
“…Visentini et al also observed a glycerol addition can decrease agglomeration and increase the intercalation of the clay into the polymer matrix during the mixing process. [26] www.advancedsciencenews.com www.ms-journal.de A synergistic effect occurs when tea tree oil is added to the mixture, as the interplanar distance of (001) diffraction peak are further increased, as show the diffractograms of PLA + MMT + EO10 (Figure 3c), PLA + MMT + EO20 (Figure 3d), PLA + MMT + EO10 + Gly (Figure 3e), and PLA + MMT + EO20 + Gly (Figure 3f) bionanocomposites. Most probably, the effective interaction between clay lamellae and the oil promotes the swelling of the nanofiller stacks.…”
Section: X-ray Diffraction Of the Bionanocompositesmentioning
confidence: 99%
“…Além disso, o óleo essencial pode atuar como plastificante no bionanocompósito. Visentini et al (2015) afirma que esse tipo de composto favorece a mobilidade das cadeias poliméricas por meio do enfraquecimento das interações intermoleculares, permitindo assim, a penetração do polímero no espaçamento interlamelar da MMT. Nos difratogramas dos bionanocompósitos de PLA+MMT+OE10 (Figura 14c) e PLA+MMT+OE20 (Figura 15d) nota-se uma forte intensidade no pico (001), o que estaria relacionada com a presença de uma morfologia altamente intercalada e ordenada.…”
Section: Difratometria De Raio-xunclassified